(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Solar energy is a significant renewable source for home and commercial applications. These solar technologies behave differently depending on the ambient temperature surrounding the devices. Thus, the varying ambient temperature necessitates research into the efficacy of various solar technologies under real-life circumstances. In this study, three types of solar technology were studied, which were polycrystalline, monocrystalline, and amorphous silicon photovoltaics (PVs). All the PVs were tested under various simulated environments (hot, room, and cold temperatures). Additionally, real environmental condition tests under direct sunlight successfully depicted the relationship between solar irradiance and ambient temperature on the PVs. Overall, monocrystalline PV outperformed polycrystalline PV, whereas amorphous PV performed poorly. This observation was evident in the lowest performance reduction of monocrystalline PV in hot (power, Ppv = 37%), room (Ppv = 82%), cold (Ppv = 95%), and direct sunlight (Ppv = 72%) conditions. Hence, this research could address the importance of selecting PVs in real-life environments in producing efficient solar PV technologies.